Overexpression of CsHMGB Alleviates Phytotoxicity and Propamocarb Residues in Cucumber - Li, Shengnan; Xin, Ming; Luan, Jie; Liu, Dong; Wang, Chunhua; Liu, Chunhong; Zhang, Wenshuo; Zhou, Xiuyan; Qin, Zhiwei (Frontiers in Plant Science, 2020)
As cucumber (Cucumis sativus L.) is one of the major economic fruits in the Cucurbitaceae family, it is important to consider potential pesticide residues in the fruits in the context of cucumber breeding and production programs. Propamocarb is one of the pesticides commonly used to prevent downy mildew in cucumber. However, the molecular mechanism underlying the degradation and metabolism of propamocarb remains unclear. Here, we screened a candidate CsHMGB gene (CsaV3-5G28190) in response to propamocarb exposure using transcriptome sequencing data. The genomic coding region of CsHMGB was 624 bp in length and contained the conserved HMB-box region. CsHMGB expression differed significantly between the ‘D0351’ genotype, which accumulates low propamocarb residues, and the ‘D9320’ genotype, which accumulates high propamocarb residues. CsHMGB expression was positively correlated with propamocarb residues in cucumber peel. CsHMGB was up-regulated in fruit peels of the ‘D0351’ genotype following exposure to propamocarb stress for 3-120 h. On the contrary, there was no difference in expression between the propamocarb stress treatment and the control for the ‘D9320’ genotype. For the ‘D0351’ genotype, CsHMGB expression was greater in fruit peels and leaves than in female flowers, expression was moderate in stems and fruit pulps, and expression was weak in male flowers and roots. The CsHMGB protein was targeted to the nucleus in both Arabidopsis protoplasts and in the epidermis of N. benthamiana leaves. By measuring MDA, O2-, and H2O2 content, cucumber plants were found to have greater accumulation of reactive oxygen species (ROS) under propamocarb stress. Analysis of antioxidant enzyme activity (SOD, POD, CAT, APX, GPX, GST, and GR) and the ASA-GSH system showed that plant resistance was reduced and propamocarb residue was increased in CsHMGB-silenced plants under propamocarb stress. Conversely, overexpression of CsHMGB reduced propamocarb residues by increasing wax levels and by opening stomata. Evaluation of antioxidant enzyme activity and the ASA-GSH system indicated that overexpression of CsHMGB enhanced cucumber plant resistance to propamocarb stress and promoted the degradation of propamocarb in cucumber.